Combining ability and gene action for structural and economical traits in brinjal (Solanum melongena) - K, GANGADHARA; ABRAHAM, MAREEN; R, SELVAKUMAR (The Indian Journal of Agricultural Sciences, 2021)
An experiment was undertaken to estimate GCA for 8 parents and SCA for 15 hybrids in brinjal (Solanum melongena L.) through line × tester analysis. The combining ability analysis revealed highly significant differences among the treatments for all the characters. The gca reveals that, parental lines L2 (IC- 433678), L5 (Raidurg Local) and T3 (Pusa Purple Cluster) were identified as good general combiners for fruit yield per plant. These lines and testers were also best combiner for yield component characters like number of primary branches per plant, days to first flower, medium and long styled flowers, fruits per plant and fruit length. The estimates of specific combining ability effects indicated that cross combinations, viz. IC-433678 × IC-89986, Tiptur Local × Vellayani Local, Jagaluru Local × Vellayani Local, IC-345271 × Pusa Purple Cluster and Raidurg Local × Pusa Purple Cluster were most promising for fruit yield per plant and its component attributes. Gene action analysis revealed preponderance of both additive and nonadditive gene actions for yield and its contributing characters.